3D Printing of Functional Magnetic Materials: From Design to Applications. (17th June 2021) - Zhang, Chengqian; Li, Xiangjia; Jiang, Laiming; Tang, Daofan; Xu, Han; Zhao, Peng; Fu, Jianzhong; Zhou, Qifa; Chen, Yong
Abstract: The research of functional magnetic materials has become a hot topic in the past few years due to their fast, long‐range, and precise response in diverse environments. Functional magnetic devices using different magnetic materials and structure designs have been developed and demonstrated good advantages to enable various applications. However, the required magnetic materials and structure designs for diverse functions also increase the fabrication difficulties while developing such devices. 3D printing technology presents a powerful and promising manufacturing approach to rapidly fabricate functional magnetic devices of complex geometries in multiple materials and scales. Here, various 3D printing strategies and the underlying mechanisms of functional magnetic materials for several primary applications are systematically reviewed, including, magnetic anisotropy for property enhancement, magnetic robots, magnetic components in electronics, and magneto‐thermal devices. Finally, the current challenges and future perspectives in engineering 3D printed functional magnetic devices are discussed. Abstract : This review explores the 3D printing of magnetic materials and summarizes their diverse applications that may benefit from 3D printing technology, including magnetic anisotropy for property enhancement, magnetic robots, magnetic components in electronics, and magneto‐thermal devices. Their relevant printing strategies and critical mechanisms are subsequently summarized, followed by existing challenges and suggested outlooks.